Gender Stereotypes in Action Movies: A Study of Wonder Woman and Black Widow - Sa’adah, Zumrotus; Permatasari, Riana; Nurhamidah, Idha (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study analyzes gender representation in Wonder Woman (2017) and Black Widow (2021), two important works that introduce female characters as main protagonists in the superhero genre. Although both feature strong, independent, and agency-filled female characters, this analysis shows that both films are still influenced by patriarchal elements that objectify women through the representation of the bodies and visual appearance of the main female characters. Using the male gaze theory introduced by Laura Mulvey (1975) and the perspective of gender analysis in media, this study aims to reveal how, despite efforts to empower women, visual depictions still highlight the sexual dimension of the female characters' bodies, reminiscent of visual structures that tend to focus on male fantasy. This study also discusses how these depictions remain trapped in a socio-cultural framework that perceives women in terms of physical beauty and sexual attractiveness. Using a qualitative approach, this study uses content analysis of key scenes in both films to trace gender representation and explore the narratives and characters that develop throughout the story. The results show that although there is room for empowerment and change in the superhero genre, women's bodies are still unavoidably objectified in these films. This research is expected to contribute to developing gender representation theory in film and offer further insight into the transformation of women's roles in Hollywood film narratives.